2020
DOI: 10.1186/s13213-020-01605-5
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the bacterial profiles and physicochemical between natural and inoculated fermentation of vegetables from Shanxi Province

Abstract: Purpose Fermented vegetables can be divided into two types, natural fermented and artificially inoculated fermented. By detecting and identifying the changes of bacterial diversity using physical and chemical indicators during natural and inoculation fermentation, we analyzed and determined the dominant bacteria in the fermentation process and revealed the relationship between bacteria and volatile substances. Methods We used the Illumina Miseq to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 49 publications
3
9
0
Order By: Relevance
“…S. alactolyticus strain FGM isolated from the chicken cecum has a good ability to ferment A. membranaceus, which improves the concentration of polysaccharides, and the fermented products are more beneficial to the health of broilers. It is reported that the health benefits of fermented food is very associated with the probiotic lactic acid bacteria (Chen et al 2020). To indicate the safety and benefits of application in animal feed in future, this study sequenced the genome of S. alactolyticus strain FGM and subjected it to genomic analyses and probiotic properties analysis.…”
Section: Discussionmentioning
confidence: 99%
“…S. alactolyticus strain FGM isolated from the chicken cecum has a good ability to ferment A. membranaceus, which improves the concentration of polysaccharides, and the fermented products are more beneficial to the health of broilers. It is reported that the health benefits of fermented food is very associated with the probiotic lactic acid bacteria (Chen et al 2020). To indicate the safety and benefits of application in animal feed in future, this study sequenced the genome of S. alactolyticus strain FGM and subjected it to genomic analyses and probiotic properties analysis.…”
Section: Discussionmentioning
confidence: 99%
“…After that, it stabilized. Lacticaseibacillus can decompose nitrite and reduce nitrite content in tomato sour soup [ 18 ]. Therefore, the inoculation of cultures with pure starters was more effective than spontaneous fermentation in controlling the nitrite concentration of fermented tomato sour soup.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, high-throughput sequencing (HTS) and gas chromatography–ion mobility spectroscopy (GC–IMS) technologies have been widely used in the detection of food microorganisms and VFCs [ 17 ], such as in fermented vegetables [ 18 ], Ma Milk wine [ 19 ], natural fermented bean curd [ 20 ], etc. Recently, HTS was used to analyze bacteria in tomato sour soup, in which Lacticaseibacillus spp.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the above results, it is possible that greater abundances of tea polysaccharides may be produced in FBT_S type teas that contribute to reducing the risk of type 2 diabetes and obesity ( Chen et al, 2019 ). In addition, some abundant microbial populations participated in amino acid metabolism activity (e.g., with glycine, serine, threonine, arginine, proline, cysteine, and methionine substrates) that can improve the taste of tea ( Chen et al, 2020 ). The metabolic pathway of ethylbenzene degradation in FBT_H samples contributed to the regulation of fermented tea aroma ( Zhu et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%